Kajian Yuridis Penggunaan Koin Kripto sebagai Alat Pembayaran di Indonesia - Kadek Dyah Pramitha Widyarani; Ida Ayu Putu Widiati; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2022)
The presence of crypto coins as a new thing in society certainly requires an attitude from a legal aspect. The rapid development of crypto coins makes many people believe that crypto coins will become a means of payment in the future. This study aims to determine the regulation of payment instruments in Indonesia and the legal consequences if crypto coins are used as payment instruments in Indonesia. This research is normative legal research, namely research with studies through literature studies based on primary and secondary legal materials. The problem approach used is a statutory approach and a conceptual approach. The results of this study show concretely that crypto coins are illegal means of payment. The use of crypto coins as a means of payment in Indonesia is not in accordance with the law and is an act that is against the law so it can have legal consequences. Crypto coins do not have a legal basis to be used as a means of payment in Indonesia. Payments using crypto coins that are prohibited by law are considered illegal payments so they can get sanctions.